2017
DOI: 10.1101/241091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disrupted brain structural connectivity in Pediatric Bipolar Disorder with psychosis

Abstract: Background: Bipolar disorder (BD) has been linked to disrupted structural and functional connectivity

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…33 Indeed, the vmPFC has been found to be functionally impaired 11,12,33 and lose its network hub property in patients with bipolar disorder. 34 We found that the functional hub strength of the vmPFC in the DMN (DMN hubiness) was significantly lower in patients than in controls. This finding suggests that the vmPFC has a provincial hub role in the DMN in controls but not in pa tients with bipolar disorder and aligns with a recent diffusion tensor imaging study reporting that the vmPFC loses its structural hub property in patients with bipolar disorder.…”
Section: Whole Brain Vertex-wise Analysismentioning
confidence: 69%
See 3 more Smart Citations
“…33 Indeed, the vmPFC has been found to be functionally impaired 11,12,33 and lose its network hub property in patients with bipolar disorder. 34 We found that the functional hub strength of the vmPFC in the DMN (DMN hubiness) was significantly lower in patients than in controls. This finding suggests that the vmPFC has a provincial hub role in the DMN in controls but not in pa tients with bipolar disorder and aligns with a recent diffusion tensor imaging study reporting that the vmPFC loses its structural hub property in patients with bipolar disorder.…”
Section: Whole Brain Vertex-wise Analysismentioning
confidence: 69%
“…Brain connectomics have revealed altered connectivity pat terns in bipolar disorder, 33 and connectomicsbased methods have revealed altered ventromedial prefrontal cortex (vmPFC) hub properties in bipolar disorder. 34 We used brain connec tomics and restingstate fMRI in posthoc secondary analyses to test the functional relevance of our main findings by calcu lating an individual's vmPFC functional hub strength, which we then related to polygenic risk scores.…”
Section: Quantification Of Vmpfc Functional-connectivity-based Hub Strength In the Default Mode Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have proven that modularity is an important feature of the brain network (Bouyssi-Kobar et al, 2019;Lin et al, 2021), the human brain presents a modular structure (Chaddock-Heyman et al, 2020), and brain network modularity is related to cognitive function. Brain damage that impairs function can cause changes in modules, especially for the study of the brain network of neurodevelopmental disorder diseases such as bipolar disorder (Fernandes et al, 2019), childhood onset schizophrenia, Alzheimer's disease (de Haan et al, 2012), and autism (Shi et al, 2013). Therefore, module-based research is of great significance for the study of mental diseases.…”
Section: Introductionmentioning
confidence: 99%